Guidelines for safe transfer of the brain‐injured patient: trauma and stroke, 2019: Guidelines from the Association of Anaesthetists and the Neuro Anaesthesia and Critical Care Society. (1st December 2019) - Nathanson, M. H.; Andrzejowski, J.; Dinsmore, J.; Eynon, C.A.; Ferguson, K.; Hooper, T.; Kashyap, A.; Kendall, J.; McCormack, V.; Shinde, S.; Smith, A.; Thomas, E.
Summary: The location of care for many brain‐injured patients has changed since 2012 following the development of major trauma centres. Advances in management of ischaemic stroke have led to the urgent transfer of many more patients. The basis of care has remained largely unchanged, however, with emphasis on maintaining adequate cerebral perfusion as the key to preventing secondary injury. Organisational aspects and training for transfers are highlighted, and we have included an expanded section on paediatric transfers. We have also provided a table with suggested blood pressure parameters for the common types of brain injury but acknowledge that there is little evidence for many of our recommendations. These guidelines remain a mix of evidence‐based and consensus‐based statements. We have received assistance from many organisations representing clinicians who care for these patients, and we believe our views represent the best of current thinking and opinion. We encourage departments to review their own practice using our suggestions for audit and quality improvement.